Rethinking Africanity Through Feminist writings Case Study Adichie’s americanah - BEN REZZAK ,IBTISSAM; Selt ,Djihed (Faculty of Letters and Foreign Languages Department of English, 2023)
Longstanding racial disparities in the United States, along with a history of black immigration have resulted numerous social issues including race and recognize owhat it means to be black for the first time. This study seeks to examine the process and difficulties of diasporic identity via the protagonists' diasporic experience in Chimamanda Ngozi Adichie's Americanah utilizing a literary analysis. The feminist postcolonial approach was applied in this study to address how members of the new African generation, particularly women, resist racism and stereotypes in America. This work concludes that feminist works were created in order to shed attention on the challenges that women face in Western cultures